Development of Contextual-Based Booklet as Learning Media to Improve Student’s Motivation in MA Al-Qodiri Kalipuro Banyuwangi - Muhimmatin, Ifa; Zihan Elmira Putri; Iis Ni’matul Jannah (Journal of Biology Education, 2025)
Interviews with biology teachers at MA Al-Qodiri Kalipuro, Banyuwangi found that they need a printed learning media about biodiversity to support student’s motivation on learning process. On the other hand, the school environment has a diversity of plants, so this diversity can be used to develop a contextual-based booklet learning resource. This research aims to determine the quality of contextual-based booklet as a learning media for students in MA Al-Qodiri Kalipuro. This is a Research and Development that using the 7 steps of the Borg and Gall research method which has been modified by Sugiyono. The 7 steps of the research method are: potential and problems, data collection, product design, design validation, design revision, product testing, product revision. The research results from the material expert validation results obtained a percentage of 97.27% in the very valid category, or can be used without revision. The assessment from media experts obtained a percentage of 98.18% in the very valid category, or can be used without revision. The user response test by students obtained a percentage score of 80.75% in the very appropriate category. Meanwhile, the user response test by the teacher obtained a percentage score of 80% in the appropriate category. Thus it can be concluded that Booklet media can be used as a learning medium that is able to motivate students to learn, so that it can make a positive contribution in increasing the effectiveness of biology learning in schools.